YUSUF DALAM KEJADIAN 37-50 SEBAGAI MODEL KEPEMIMPINAN DAN KEWIRAUSAHAAN BAGI ENTREPRENEUR KRISTEN INDONESIA - Kristiawan, Ragil; Pujiati, Pujiati (SEKOLAH TINGGI TEOLOGI DAN ENTREPRENEURSHIP PRINGGADING (STEP) SEMARANG, 2026)
This research is motivated by the need for an entrepreneurial paradigm that integrates business success with resilient spiritual and ethical values, particularly for Christian entrepreneurs in Indonesia who often face dissonance between faith and business practices. The narrative of Joseph in Genesis 37-50 is seen as a potential source for an integrative model, yet systematic study through an entrepreneurial lens remains an academic gap. Therefore, this research aims to answer the question: how can the narrative of Joseph's life be interpreted as an inspiring model of entrepreneurship and leadership for Christian entrepreneurs in Indonesia? The method used is qualitative library research with an interdisciplinary approach, hermeneutically analyzing the text of Genesis and synthesizing it with management concepts and leadership theories. The discussion constructs three main pillars of the model: (1) resilience and long-term vision as the foundation of entrepreneurial spirit, (2) integrity and the principle of stewardship as a paradigm for ethical resource management, and (3) servant leadership and reconciliation as the foundation for transformational social capital. The research conclusion indicates that these three pillars form a holistic model that can function as a reflective framework and diagnostic tool for developing entrepreneurship that is not only materially successful but also spiritually and socially meaningful within the Indonesian context.